2019
DOI: 10.3892/ol.2019.11001
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA heart and neural crest derivatives expressed�2‑antisense RNA�1 overexpression inhibits the proliferation of cancer cells by reducing RUNX2 expression in triple‑negative breast cancer

Abstract: The role of long non-coding RNA heart and neural crest derivatives expressed 2-antisense RNA 1 (lncRNA HAND2-AS1) in tumor suppression has been reported in a number of cancer types, while its functionality in triple-negative breast cancer (TNBC) remains unclear. The present study aimed to investigate the involvement of lncRNA HAND2-AS1 in TNBC using different methodologies. HAND2-AS1 and RUNX2 expression was analyzed using reverse transcription-quantitative PCR and western blot analysis. Diagnostic analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In this study, we mainly analyzed HAND2-AS1 and discovered that it is downregulated in BC cell lines, which was in accordance with previous reports [ 19 , 20 ]. In addition, HAND2-AS1 could suppress proliferation, migration, and invasion but accelerated death in BC cells, which was consistent with the findings in the previous study about the HAND2-AS1 role in cancers [ 20 , 21 ]. In addition, there has not been research involving the effect of HAND2-AS1 in a breast cancer animal model.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we mainly analyzed HAND2-AS1 and discovered that it is downregulated in BC cell lines, which was in accordance with previous reports [ 19 , 20 ]. In addition, HAND2-AS1 could suppress proliferation, migration, and invasion but accelerated death in BC cells, which was consistent with the findings in the previous study about the HAND2-AS1 role in cancers [ 20 , 21 ]. In addition, there has not been research involving the effect of HAND2-AS1 in a breast cancer animal model.…”
Section: Discussionsupporting
confidence: 89%
“…In Jin et al reported that lncRNA HAND2-AS1 expression was reduced in patients with cervical cancer compared to normal subjects and that it inhibited the proliferation, migration and invasion of cancer cells by downregulating ROCK1 (13). In a study by Min et al, patients with Triple-negative breast cancer (TNBC) had significantly lower plasma levels of lncRNA HAND2-AS1 and were able to act as oncogenes in TNBC by downregulating RUNX 2 to inhibit cancer cell proliferation compared to healthy controls (14). Small nucleolar RNA host gene 7 (SNHG7) is a novel oncogenic lncRNA located on chromosome 9q34.3, which is 2,176 bp long (15).…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we predicted that a binding between miR-106a-5p and HAND2-AS1. And it has been reported that HAND2-AS1 was involved in the progression of breast cancer [ 31 , 32 ]. And our results showed HAND2-AS1 acted as a sponge of miR-106a-5p, and HAND2-AS1 was decreased in TNBC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%